Research of microflame low-emission natural gas combustion technology adapted for chinese-type power boilers - Romanova, K.; Zongyan, Wu (Energy and Automation, 2026)
The relevance of the study is обусловлена the need to reduce nitrogen oxide emissions during natural gas combustion in thermal power installations and to improve the energy and environmental efficiency of gas-fired equipment. The implementation of low-emission combustion technologies capable of ensuring stable fuel combustion with minimal pollutant formation is of particular importance. The aim of the study is to investigate the processes of microflame low-emission natural gas combustion and to evaluate the efficiency of a high-velocity jet burner in reducing NOx formation, equalizing the temperature field, and improving the environmental characteristics of the combustion process. To achieve this goal, numerical CFD simulation of combustion processes was carried out in the ANSYS Fluent software environment using the RANS approach and the standard k–ε turbulence model. The influence of burner geometric parameters and excess air ratio on the temperature regime and NOx formation processes was investigated. Experimental studies of a 200 kW microflame burner were performed using a GASMET DX4000 gas analyzer. It was established that the proposed burner design ensures the formation of multiple microflames, intensifies fuel-air mixing, and provides a more uniform temperature distribution in the combustion chamber. It was determined that the most efficient operating mode is achieved with an air channel diameter of 16 mm and an excess air ratio of α ≈ 1.4. The obtained results showed that the NOx concentration in combustion products does not exceed 50 mg/m³, which complies with current requirements for low-emission combustion technologies. The practical significance of the study lies in the possibility of using the proposed microflame burners for modernization of existing thermal engineering installations and improvement of the environmental safety of natural gas combustion processes.Recieved: 03.01.2026.  Recieved: 09.03.2026. Accepted: 17.04.2026.
Keywords: microflame combustion; low-emission burner; natural gas; nitrogen oxides; CFD simulation; excess air ratio; temperature field; CFD-моделювання; температурне поле